2021
DOI: 10.1038/s41467-021-25287-y
|View full text |Cite
|
Sign up to set email alerts
|

Thousands of Qatari genomes inform human migration history and improve imputation of Arab haplotypes

Abstract: Arab populations are largely understudied, notably their genetic structure and history. Here we present an in-depth analysis of 6,218 whole genomes from Qatar, revealing extensive diversity as well as genetic ancestries representing the main founding Arab genealogical lineages of Qahtanite (Peninsular Arabs) and Adnanite (General Arabs and West Eurasian Arabs). We find that Peninsular Arabs are the closest relatives of ancient hunter-gatherers and Neolithic farmers from the Levant, and that founder Arab popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 78 publications
1
38
0
Order By: Relevance
“…Similarly, the median number of singletons is lower for PAR cluster compared with other subclusters reflects the closely related individual present in this cluster (Table 2). Furthermore, runs of homozygosity (ROH) analysis of the QGP done by Razali et al (2021), identified per population ROH boundary for short, medium, and long ROH. We observed that Peninsular Arabs (PAR) have the lowest median for short ROH after African-based populations.…”
Section: Genetic Ancestry and Diversity Of The Qatari Populationmentioning
confidence: 99%
“…Similarly, the median number of singletons is lower for PAR cluster compared with other subclusters reflects the closely related individual present in this cluster (Table 2). Furthermore, runs of homozygosity (ROH) analysis of the QGP done by Razali et al (2021), identified per population ROH boundary for short, medium, and long ROH. We observed that Peninsular Arabs (PAR) have the lowest median for short ROH after African-based populations.…”
Section: Genetic Ancestry and Diversity Of The Qatari Populationmentioning
confidence: 99%
“…More recently, a study sequencing whole genomes from 6218 Qatar individuals identified 74,783,226 variants, of which 28% were not present in current databases, mainly 1KG project, Human Origin dataset, and GME [20]. These studies and our analyses highlight the importance of expanding genomic sequencing studies among diverse underrepresented populations, which include variation that has not yet been sampled.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, Fattahi and his colleagues performed whole-exome sequencing on 800 individuals from eight major Iranian ethnic groups and identified 1,575,702 variants, of which 308,311 were novel (19.6%), compared to current databases, including gnomAD [ 19 ]. More recently, a study sequencing whole genomes from 6218 Qatar individuals identified 74,783,226 variants, of which 28% were not present in current databases, mainly 1KG project, Human Origin dataset, and GME [ 20 ]. These studies and our analyses highlight the importance of expanding genomic sequencing studies among diverse underrepresented populations, which include variation that has not yet been sampled.…”
Section: Discussionmentioning
confidence: 99%
“…The Qatari Cohort: The Qatar Genome Program (QGP) [21] is a population-based project launched by the Qatar Foundation to generate a large-scale whole-genome sequence (WGS) dataset, in combination with comprehensive phenotypic information collected by the Qatar Biobank (QBB) [22]. All subjects included in the analysis were of Qatari Middle Eastern Arabian ancestry [23]. In this study, we use a cohort of 14,398 individuals with an average coverage of 30X.…”
Section: Population Descriptionmentioning
confidence: 99%
“…We used data from the gnomAD v3.1 [35] call set, including 1000Genomes project samples and extracted information on the EUR, AFR and SAS superpopulations subset. The EUR subset was used as reference for the Italian samples [36], while the AFR and SAS subsets for the Qatari cohort [23]. We defined two different levels of comparison: at the ancestry level, in which we selected all genes showing concordant selective signals between our study cohorts and their closest ancestry population, and at the population level, in which we selected only genes showing different behaviour between our target population and the reference.…”
Section: Genes Selection and Prioritization Analysesmentioning
confidence: 99%